METABOLISME LIPID PADA DAGING BABI DAN KEMUDHARATANNYA BERDASARKAN PENJELASAN AL-QURAN DAN SAINS - Assyifa Junitasari (Khazanah Multidisiplin, 2021)
Metabolism plays a role in changing food substances such as glucose, amino acids, and fatty acids into compounds needed for life processes such as energy sources (ATP). Metabolic processes that occur in all body tissues which occur under the same conditions or reaction conditions require physicochemical and chemical requirements that are not much different from each other. Fat is considered by many to be a component of a diet that must be reduced as much as possible. However, this is not beneficial for health because of a certain amount of fat, usually about 30% of the total energy needed to carry out its functions properly in the body. Sources of fat usually there are many from animal sources, one of which contains a lot of pork fat content in it. However, according to Islamic teachings and written in Al-Quran that pork should not be consumed because it is included in illicit food. This paper aims to find out the understanding of fat metabolism, to find out the fat content in the body of pigs, and to know the unlawfulness of pork in Al-Quran. The writing method used is the method of literature, the author gets information through various references from the internet, as well as Al-Quran and commentary books. This paper was made as a reference or guide for readers and also lecturers and students of UIN Sunan Gunung Djati Bandung, especially the chemistry department of the Faculty of Science and Technology in the learning process as a manifestation of Revelation Guiding Science (WMI). In addition, we can practice in life.